Crystal structure of chlorido(2-{[2-(4-chlorophenyl)hydrazin-1-ylidene-κN1](phenyl)methyl}pyridine-κN)(η5-pentamethylcyclopentadienyl)iridium(III) tetraphenylborate. (March 2015) - Devika, Neelakandan; Raja, Nandhagopal; Ananthalakshmi, Subbiah; Therrien, Bruno
No abstract available